BRCA Mutation Testing for First-Degree Relatives of Women With High-Grade Serous Ovarian Cancer [4OP]. (May 2018) - Kwon, Janice S.; Tinker, Anna; Hanley, Gillian; Pansegrau, Gary; Carey, Mark S.; Schrader, Kasmintan
Abstract : INTRODUCTION: Women with high-grade serous ovarian cancer (HGSC) have a 20% chance of carrying a BRCA1 or BRCA2 mutation and are eligible for BRCA testing. Many are untested, therefore their female first-degree relatives (FDR) may not qualify for testing unless they have specific ethnicity or other personal/family cancer history. We conducted a cost-effectiveness analysis to evaluate BRCA mutation testing for these FDR who are otherwise ineligible for testing. METHODS: A Markov Monte Carlo simulation model estimated the costs and benefits of 3 strategies for female FDR of HGSC patients whose BRCA status is unknown: 1) no BRCA testing; 2) universal BRCA testing, followed by risk-reducing bilateral salpingo-oophorectomy (RRBSO) for mutation carriers ("BRCA testing"); 3) universal RRBSO, without BRCA testing ("RRBSO"). Effectiveness was estimated in quality-adjusted life year (QALY) gains. Sensitivity analyses accounted for uncertainty around various parameters. The time horizon was 50 years. RESULTS: BRCA testing for female FDR of HGSC patients yielded a higher average QALY gain at acceptable cost compared to no BRCA testing, with an ICER of 7, 729 per QALY. BRCA testing was more effective and less costly than RRBSO (19.20 QALYs vs 18.48 QALYs, and 10, 108.35 vs 13, 959.20, respectively), therefore BRCA testing is the dominant strategy. Results were stable over a wide range of plausible costs and estimates. Compliance with hormone replacement therapy had to exceed 84% for RRBSO to be the preferred strategy. CONCLUSION: BRCA mutation testing should be offered to all female first-degree relatives of women with high-grade serous ovarian cancer when their BRCA mutation status is unknown.